The Electric Vehicle Lithium Battery Monitoring System - Lei Lin; Yuankai Liu; Wang Ping; Fang Hong (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
With the global increase in the number of vehicles, environmental protection and energy issues had become increasingly prominent. People paid more and more attention to the electric vehicle as the future direction of the vehicle, but because the battery technology was relatively backward, it had become the bottleneck in the development of electric vehicles. So in the existing conditions, a perfect battery Monitoring technology had become more and more important. This paper firstly analyzed the characteristics of lithium battery residual capacity and effect factors, then put forward to a set of solutions according to the actual situation. The solution of the lithium battery Monitoring system adopted distributed structure, including detection of voltage, current, temperature and measurement module and the realization of monomer battery equalizer module. Using a single bus device DS2438 produced by DALLAS on the battery voltage, current, temperature, power and other parameters, the system controlled DS2438 by the STC89C52 single-chip in data acquisition. Then it used the algorithm to predict state of charge(SOC) and displayed the battery status in the LCD1602. This solution of the lithium battery Monitoring system  was reliable, economy, strong anti-interference ability. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2545